Mechanistic insights into nigerian lithium ores: implications for energy and industrial applications - Olajuyi, S. I.; Adamu, H. A.; Ogunmodimu, O. S.; Afolayan, D. O. (Frontiers in Geochemistry, 2025)
Lithium is a critical element in battery technology for renewable energy storage applications. The mineral offers potential solutions to the current surge in global energy demand and can position Nigeria as a potential key player in the lithium supply chain. However, little to nothing is known of the lithium deposits in Nigeria. This review explores the formation, geology, and ongoing exploration activities of lithium in Nigeria. The study provides an overview of the geological settings and mineralogical characteristics of the Nigerian lithium-bearing pegmatites and ores, comparing them with global deposits. It also examines current lithium mining and processing techniques, identifies significant developmental challenges and recommends potential solutions to lithium exploration in Nigeria. Additionally, the paper discusses Nigeria’s policy landscape, investment gaps, and the government’s efforts to establish a sustainable lithium processing industry. The findings emphasise the need for best mineral extraction practices, improved beneficiation technologies, and strategic policy reforms to enhance Nigeria’s position in the global lithium market. The study concludes that with proper investment and regulatory frameworks, Nigeria has the potential to become a significant lithium supplier and contribute to the global transition towards clean energy.